2012
DOI: 10.1152/ajpheart.00339.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral short hairpin RNA therapy targeting phosphodiesterase 5a relieves cardiac remodeling and dysfunction following myocardial infarction

Abstract: short hairpin rna therapy targeting phosphodiesterase 5a relieves cardiac remodeling and dysfunction following myocardial infarction. Am J Physiol Heart Circ Physiol 302: H2112-H2121, 2012. First published March 23, 2012 doi:10.1152 doi:10. /ajpheart.00339.2011 showed that treatment with tadalafil, a long-acting phosphodiesterase-5a (PDE5a) inhibitor, effectively prevented adverse left ventricular (LV) remodeling of the infarcted heart. We hypothesized that short-hairpin RNA (shRNA) therapy targeting PDE5a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…; Li et al. ; Kumar and Ashraf ). VASP downstream of PKG1 may be involved in the intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Li et al. ; Kumar and Ashraf ). VASP downstream of PKG1 may be involved in the intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…; Li et al. ); the mechanisms underlying tadalafil's effects on stem cell survival in vivo are incompletely understood. In this study, we attempt to define the novel pathways by which tadalafil treatment leads to cardioprotection.…”
Section: Introductionmentioning
confidence: 99%
“…Though in vitro gene-deletion studies have supported specificity and selectivity for PDE5, attempts to generate in vivo PDE5 knockout models have been repeatedly unsuccessful. However, a new study [50] used small interfering RNA (siRNA) against PDE5 delivered intramyocardially by adenovirus and found improved cardiac remodeling postinfarction, with enhanced cGMP/PKG signaling. Furthermore, studies have utilized the more selective tadalafil reporting similar efficacy.…”
Section: Pde5 and Myocardial Disease: Experimental Studiesmentioning
confidence: 99%
“…Treatment with PDE-5 inhibitors, sildenafil or tadalafil, effected cardioprotection both in vitro and in vivo through PKG1 [27], [28], [29]. In a previous study we showed that PDE5a inhibition with adenoviral short hairpin RNA could protect cardiomyocytes against anoxia, attenuate infarction size and improve cardiac remodeling and dysfunction [30].…”
Section: Introductionmentioning
confidence: 97%